Study of Health Parameters Changes for Local Male Rabbits when Supplied Water with Potassium Permanganate (Kmno4) and Chlorine - Jummah, Mohammed Abdulhamza; Tuaimah, Ghaith Sabah; Jaafar, Shahad Kadhim (American Journal of Biology and Natural Sciences, 2025)
Thirty-two local male rabbits were four groups were created at random.: GM1 first group (water free of chlorine) control group, GM2 second group (provided tap water), GM3 third group (Potassium permanganate (1) P.P.M.), and GM4 fourth group (Potassium permanganate (2)P.P.M.) to investigate the disinfection effectiveness of Potassium permanganate or chlorine in tap water on a few physiological and liver enzymatic parameters. Serums were obtained after blood samples taken. The values (Hb: 18.61 gm/dl, PCV percent: 43.58, total protein: 8.03 gm./dl, albumen: 5.19 gm./dl , and globulen : 3.76 gm./dl) in the tap water group were substantially (P0.05) greater than in the other groups. When compared to the other groupings, the tap water group had considerably lower levels of ALT (40.09IU/L), AST (26.76 IU/L), and ALP (31.52 IU/L).